The Influence of Leadership Style on Public Service at the Teluk Ambon District Office, Ambon City - Julent Audri Matakena; Petronela Sahetapy; Julia Theresia Patty (Journal of Scientific Interdisciplinary, 2026)
This study examines the influence of leadership style on public service at the Teluk Ambon District Office, Ambon City. The research was motivated by practical service problems at the district level, including uneven implementation of frontliner service procedures, varying employee discipline, and weak coordination among organizational units. A quantitative survey design was applied to test the causal relationship between leadership style and public service quality. Data were collected from 50 respondents consisting of 24 district employees and 26 community service users through structured questionnaires supported by observation, interviews, and documentation. Leadership style was measured through decision-making ability, motivational ability, subordinate control, and emotional control, whereas public service quality was measured using the SERVQUAL dimensions of tangibles, reliability, responsiveness, assurance, and empathy. The data were processed using IBM SPSS with validity, reliability, normality, simple linear regression, t-test, and coefficient of determination procedures. The findings show that all questionnaire items were valid and reliable. The regression model produced a positive coefficient, a standardized beta of 0.906, and an R Square value of 0.820, indicating that leadership style explained 82.0% of the variation in public service quality. The novelty of this study lies in its focus on district-level public service governance in an archipelagic urban context, where leadership is not only administrative but also coordinative and adaptive. The study implies that stronger leadership supervision, staff arrangement, and service discipline are necessary to improve the consistency of public service delivery.